Overview of Mothers' Knowledge About Diarrhea in Toddlers at Helen Clinic - Icelusari Situmorang; Merlina Sinabariba; Desriati Sinaga; Ermawaty Arisandi (CV. AFDIFAL MAJU BERKAH, 2025)
Diarrhea remains one of the leading causes of death among toddlers in Indonesia, especially in North Sumatra Province. Mothers' lack of knowledge about the treatment and prevention of diarrhea can worsen the condition of toddlers suffering from diarrhea. This study aims to determine mothers' knowledge about diarrhea in toddlers and the characteristics of mothers based on age, education, and occupation at Helen Tarigan Clinic in 2025. This study used a descriptive survey method with a quantitative approach. Sampling was conducted using purposive sampling of mothers who had infants aged 12–59 months. Data were collected using a questionnaire that had been tested for validity and reliability. The results showed that of the 30 respondents, 33.3% had good knowledge, 40% had adequate knowledge, and 26.7% had poor knowledge. Most respondents were aged 21–35 years (66.7%), had a high school education (55.3%), and worked as housewives (36.7%). Conclusion: Most mothers have sufficient knowledge about diarrhea in toddlers. Therefore, mothers are expected to be more active in seeking information about diarrhea in toddlers, and health workers/clinics are expected to always provide education or counseling during immunization or by providing leaflets at clinics so that mothers who visit the clinic can read useful information and gain insight about diarrhea in toddlers.